Synthesis of Material Composite rGO-TIO2 From Coconut Shells by Sol-Gel Methods as Photocatalyst - Hikmah, Utiya; Yanti, Diah Risma; Axala, David Lee Giant (Department of Physics, Sebelas Maret University, 2024)
The rGO- TiO2 composite photocatalyst is receiving great attention because of its high performance. But the study of rGO- TiO2 composite with sources of rGO material derived from the utilization of organic waste such as coconut shells is limited. In this study, the synthesis of nanocomposite rGO- TiO2 was described with rGO obtained from coconut shells. The rGO samples produce through the oxidation and reduction process. The transformation of graphene oxide into reduced graphene oxide was assisted by microwave irradiation. The obtained rGO was then composite with Titanium tetraisopropoxide (TTIP) by the sol-gel method. The composite of rGO- TiO2 was characterized by XRD, FTIR, UV-Vis, and SEM. The photocatalytic performance of the rGO- TiO2 composite was conducted on Methylene blue. The result shows that rGO- TiO2composite has a good photocatalytic performance with the highest number at 96%.